Analysis of the sensitization activity of Moringa oleifera leaves protein - Lu, Juan; Liu, Xiaoxue; Li, Wenjie; Xi, Chuyu; Feng, Dan; Song, Shuang (Frontiers in Nutrition, 2025)
The determination of allergenic proteins in Moringa oleifera leaves, which is the main components of immune activity, has enabled the development of a more effective method for evaluating the activity of extracted Moringa oleifera leaves protein. In this study, the extraction process of Moringa oleifera leaves protein was optimized based on a single factor experiment. The hemagglutination-related properties of Moringa oleifera leaves protein, such as (thermal, acid–base) stability, sugar binding specificity, ion binding characteristics, and hemolytic activity, were detected. The optimal combination of extraction process was: extraction time of 6 h, material-liquid ratio of 1:8, and ammonium sulfate saturation of 60%. The extraction rate of moringa leaf protein under this condition was 14.37 mg/g. The molecular weight of moringa leaf protein was analyzed by SDS-PAGE, and the molecular weight was mainly concentrated around 23 kDa 70 kDa, with the highest content of 35 kDa (major allergen). The study of the hemagglutination characteristics of Moringa oleifera leaves protein revealed that the protein exhibited high stability at temperatures below 60°C, with complete loss of activity occurring at temperatures above 110°C for 20 min. The effect of different pH conditions on the hemagglutination capacity of Moringa oleifera leaves protein was readily discernible. The hemagglutination activity of Moringa oleifera leaves protein was 104 in a pH value from 3.7 to 7.8, and the hemagglutination activity was completely lost at a pH value higher than 11.9. D(+) anhydrous glucose is the specific inhibitory sugar of Moringa oleifera leaves protein lectin. Moringa oleifera leaves protein exhibits hemolytic activity at a concentration of at least 20 mg/mL, and α-methyl-mannoside, galactoside, raffinose and Al3+ can inhibit the hemolysis of Moringa oleifera leaves protein. The present study identified the effects of different factors on the coagulation activity and hemolytic ability of Moringa oleifera leaves protein, thereby providing a theoretical basis for further purification and application of Moringa oleifera lectin. However, it should be noted that the results of the mixture have certain limitations, and further purification of lectin is needed to obtain more targeted research results.